A Predictive Maintenance Framework for Offshore Industrial Equipment: Digital Transformation for Enhanced Reliability - David Chinalu Anaba; Mercy Odochi Agho; Ekene Cynthia Onukwulu; Peter Ifechukwude Egbumokei (Engineering And Technology Journal, 2025)
This review presents a novel predictive maintenance framework designed to enhance the reliability of offshore industrial equipment by integrating artificial intelligence (AI), the Internet of Things (IoT), and 3D modeling. In offshore energy operations, maintaining equipment reliability is paramount due to the harsh environmental conditions and the critical nature of uninterrupted service. Traditional maintenance approaches, such as reactive or preventive methods, often fall short in addressing the complexity and unpredictability of offshore environments. The proposed framework leverages real-time monitoring, lifecycle management, and predictive analytics to anticipate equipment failures before they occur, optimizing operational uptime and minimizing downtime costs. The framework focuses on three key components: AI-driven predictive analytics, IoT-based real-time data collection, and 3D modeling for virtual equipment monitoring. AI algorithms analyze vast datasets from sensors to detect patterns and predict potential failures, allowing for proactive maintenance scheduling. IoT sensors continuously monitor equipment health, providing real-time insights into operational conditions, such as vibrations, temperature, and pressure. Furthermore, 3D modeling offers a visual representation of offshore equipment, helping to forecast potential failures and visualize maintenance needs more effectively. This integrated approach addresses the unique challenges of offshore operations by providing more accurate predictions, reducing risks associated with equipment failure, and enhancing the overall efficiency of offshore energy operations. The framework’s novelty lies in its fusion of cutting-edge technologies, which together form a comprehensive solution to redefine reliability engineering in offshore industries. The model aims to drive the digital transformation of maintenance practices, improving safety, reducing costs, and ensuring the continued performance of critical offshore infrastructure.